2012
DOI: 10.1002/anie.201205348
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Hydrogenation of Electron‐Poor Allenes and Alkenes

Abstract: The poorer, the better: A metal-free catalytic procedure for the reduction of electron-poor allenes and alkenes has been developed. The method employs a frustrated Lewis pair based catalyst. 1,4-Diazabicyclo[2.2.2]octane (DABCO)/B(C6F5)3 was shown to be the best combination in optimization studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 50 publications
2
60
0
2
Order By: Relevance
“…Good conversions were obtained using 2,6-lutidine as the amine base (Scheme 22). In a similar fashion, Alcarazo and coworkers [57] showed that the combination of B(C 6 F 5 ) 3 and DABCO or 2,6-lutidine (10-15 mol %) effectively hydrogenated allenic esters, such as 56 to the corresponding esters 57, respectively (Scheme 22). In a related sense, several enones were completely reduced in a domino hydrogenation/ hydrosilylation catalyzed by [2,2]-paracyclophane bisphosphine/B(C 6 F 5 ) 3 FLP catalysts (Scheme 23).…”
Section: Electron-poor Alkenes and Alkynesmentioning
confidence: 89%
“…Good conversions were obtained using 2,6-lutidine as the amine base (Scheme 22). In a similar fashion, Alcarazo and coworkers [57] showed that the combination of B(C 6 F 5 ) 3 and DABCO or 2,6-lutidine (10-15 mol %) effectively hydrogenated allenic esters, such as 56 to the corresponding esters 57, respectively (Scheme 22). In a related sense, several enones were completely reduced in a domino hydrogenation/ hydrosilylation catalyzed by [2,2]-paracyclophane bisphosphine/B(C 6 F 5 ) 3 FLP catalysts (Scheme 23).…”
Section: Electron-poor Alkenes and Alkynesmentioning
confidence: 89%
“…Building on these initial findings, Paradies [34][35][36] demonstrated that the order in which the proton and hydride are delivered could be reversed in FLP reductions of a series of nitro-olefins. Alcarazo and coworkers 37 used B(C 6 F 5 ) 3 and a N-base to catalytically hydrogenate allenic esters and Paradies' group used B/P FLPs to hydrogenate enones. 38 Soos showed that B(C 6 F 5 ) 3 and DABCO catalytically reduce imines, enamines and N-heterocycles.…”
Section: Flp Hydrogenationsmentioning
confidence: 99%
“…replaced with as econdary or tertiary ammonium or phosphonium chloride 4-6 (Scheme 2, bottom), the corresponding triarylborohydrides 7,w hich were previously synthesized by the cleavage of H 2 by FLPs, [5,6] were obtained in good yield in analytically pure form.…”
mentioning
confidence: 99%